Simulation and analysis of the optical performance of silicon nanowire arrays - Wang, Shanshan; Zhang, Yan; Zhu, Liping (Journal of physics. Conference series, 2023)
It is the basic operating principle of many optoelectronic sensors with using semiconductor materials to detect light waves for achieving efficient photoelectric conversion. At present, how to maximize the light absorption of materials in broad spectrum becomes one of the key subjects in optical sensing field. In this paper, the antireflective properties of silicon nanowire arrays is analyzed by means of the subwavelength grating principle and the effective medium theory, and the influence of structural parameters on the reflectivity of micro/nano structured arrays under broad spectrum irradiation is simulated by finite difference time domain solutions simulation software system. Theoretical calculation can get knowledge of the variation regularity of diffraction order of micro/nano films. Simulation result can provide theoretical reference for later specific experiments of realizing the morphology evolution of arrays. Combination of two steps, the appearance of higher-order diffraction light can be controlled by changing the structural parameters so as to improve the antireflective properties of micro/nano structured arrays.